Bacteroides faecium sp. nov. isolated from human faeces. Issue 1 (10th January 2023) - Kim, Juseok; Song, Hye Seon; Kim, Joon Yong; Whon, Tae Woong; Chung, Won-Hyong; Nam, Young-Do; Choi, Yoon-E; Roh, Seong Woon
Abstract : A novel bacterial strain, CBA7301 T, was isolated from human faeces and was characterised using a polyphasic taxonomic approach. A phylogenetic analysis based on 16S rRNA gene sequences revealed that CBA7301 T represented a member of the genus Bacteroides, in the family Bacteroidaceae . The similarity between the 16S rRNA gene sequence of CBA7301 T and that of its most closely related species, Bacteroides faecichinchillae JCM 17102 T, was 96.2 %, and the average nucleotide identity between these two strains was 77.9 %. The genome size was 6 782 182 bp, and the DNA G+C content was 42.5 mol%. Cells of CBA7301 T were Gram-stain-negative, strictly anaerobic and rod-shaped. The optimal growth of this organism occurred at 30–35 °C, pH 7.0 and 0.5 % (w/v) NaCl. The respiratory quinone was menaquinone 10. The predominant polar lipids were phosphatidylethanolamine, phospholipids and aminophospholipids. The major cellular fatty acid was anteiso-C15 : 0 . According to the results of the polyphasic taxonomic analysis, CBA7301 T represents a novel species of the genus Bacteroides, which we named Bacteroides faecium sp. nov. The type strain is CBA7301 T (=KCCM 43355 T =ATCC TSD-227 T ).